Short‐ and Long‐term Effects of Neuromodulators for Unexplained Chronic Cough. (10th April 2018) - Bowen, Andrew Jay; Nowacki, Amy S.; Contrera, Kevin; Trask, Douglas; Kaltenbach, James; Milstein, Claudio F.; Adessa, Michelle; Benninger, Michael S.; Taliercio, Rachel; Bryson, Paul C.
Abstract : Objective: To evaluate the short‐ and long‐term effects of tricyclic antidepressants (TCAs) and gabapentin in the treatment of unexplained chronic cough (UCC). Study Design: Prospective cohort. Setting: Tertiary care hospital. Subjects and Methods: Patients seen between July 2016 and March 2017 were included following a formal workup and clinical evaluation indicative of UCC. Patients were placed on either a TCA (amitriptyline or nortriptyline) or gabapentin. Leicester Cough Questionnaire (LCQ) and percentage improvement scores were obtained prior to treatment initiation and at 2 and 6 months of neuromodulator treatment. A linear mixed model assessed the change in LCQ score between the 2 treatment time points and baseline scores. Results: Twenty‐eight patients completed a total of 37 neuromodulator trials. Gabapentin demonstrated statistically significant improvement in LCQ scores at 2 months (2.48 points, P ≤. 01) and 6 months (5.40 points, P =. 01) of treatment as compared with baseline. Patients taking TCAs demonstrated statistically significant improvement of LCQ scores at 2 months of treatment (3.46 points, P ≤. 01). However, the majority of patients discontinued treatment, most commonly secondary to the development of tachyphylaxis after 2 months, precluding analysis at 6 months. Conclusion: While both neuromodulator classes demonstrated short‐term benefit, the majority of patients discontinue treatment prior to 6 months, with patients taking TCAs discontinuing more frequently than patients on gabapentin. Future investigations are warranted evaluating tachyphylaxis and the utility of dual treatment therapies designed to address peripheral and central sensory pathways involved in UCC.